Effect of Nocardia on immune response of Heat Killed Candida albicans Antigen against systemic candidiasis - Yassein, Shaimaa Nabhan (The Iraqi Journal of Veterinary Medicine, 2011)
This study was undertaken to prepare Heat Killed Candida albicans Antigen (HK-CA) and to investigate it's effect on elicitation of Delayed-type Hypersensitivity (DTH) and protection from virulent Candida challenged in mice, and described the major effect of Nocardia on the immunogenicity of this Ag.Four groups of 6 males Swiss mice for each group were immunized intraperitonialy(I.p)for 10 days at 5 doses(one day intervals) with 1x108 HK-CA plus Nocardia cell sap as adjuvant(CFA),the second group immunized with HK-CA plus Freund incomplete adjuvant,the third group immunized with HK-CA only and the fourth group treated with normal saline. Another group of 6 animals was immunized intranasally(I.n)with HK-CA only with the same doses as previously.Two weeks following the last application of Ag,50% of animals(3 for each group) were challenged intravenously(I.v)with 106 viable C.albicans to assess the protection rate.and the other 50% of mice were used to evaluate the development of DTH response in each immunization methods.Greatly percentage survival was observed when mice immunized with HK-CA plus CFA,which challenged with 106 live C. albicans in comparison with other groups.And also all animals of the 1st group developed highly significant DTH response which was supporyed by marked infiltration and aggregation of lymphocyte in some internal organs that indicate it's intensive involvement in immune response,while in the other groups,mononuclear cells infiltration were present with moderate to less intensive. Clearly,HK-CA in conjunction with Nocardia cell sap as adjuvant afforded significant levels of protection,Furthermore,the noval approach of I.n immunization could used for the development of an effective vaccine